2017
DOI: 10.1111/micc.12363
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic approaches to the study of angiogenesis and the microcirculation

Abstract: Microfluidic systems have emerged as a new class of perfusable in vitro culture models that have helped advance and refine our understanding of microvascular function. Cutting-edge microfluidic models have successfully integrated principles from quantitative analysis of vascular function, in vitro flow chambers, microfabrication techniques, and 3D tissue scaffolds. Here, we review the evolution of microfluidic systems, namely their progression from 2D planar microchannel arrays to 3D microtissue analogs, and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 57 publications
0
30
0
Order By: Relevance
“…However, one challenge for studies conducted in vivo is the involvement of confounding inflammatory reactions that are difficult to discriminate from the direct physicochemical effects on LECs . In contrast, microfluidic models are comprised of the necessary 3‐D matrix and cell components that are assembled using a microscale “bottom‐up” approach to enable exquisite control over the chemical and physical environment such as tuning of ECM properties, spatial patterning of cellular constituents, and specification of biomolecular gradients . Therefore, 3‐D microfluidic devices permit visualization of lymphatic sprouting, quantification of vessel permeability, and ECM remodeling since they are readily compatible with labeling and imaging techniques such as immunofluorescence, confocal reflectance microscopy, and second harmonic generation imaging.…”
Section: Microfluidic Approaches For Studying Lymphatic Vasculaturementioning
confidence: 99%
See 2 more Smart Citations
“…However, one challenge for studies conducted in vivo is the involvement of confounding inflammatory reactions that are difficult to discriminate from the direct physicochemical effects on LECs . In contrast, microfluidic models are comprised of the necessary 3‐D matrix and cell components that are assembled using a microscale “bottom‐up” approach to enable exquisite control over the chemical and physical environment such as tuning of ECM properties, spatial patterning of cellular constituents, and specification of biomolecular gradients . Therefore, 3‐D microfluidic devices permit visualization of lymphatic sprouting, quantification of vessel permeability, and ECM remodeling since they are readily compatible with labeling and imaging techniques such as immunofluorescence, confocal reflectance microscopy, and second harmonic generation imaging.…”
Section: Microfluidic Approaches For Studying Lymphatic Vasculaturementioning
confidence: 99%
“…Microfluidic devices are most commonly fabricated by rapid prototyping of PDMS, an optically transparent and gas permeable elastomer . These devices contain networks of micron‐scale fluid‐filled channels that are similar in size and architecture to lymphatic vessels in vivo . Moreover, microfluidic techniques enable controlled application of fluid flow and wall shear stress to cultured endothelial cells in a platform that can be readily scaled up for high‐throughput screening studies .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first group of articles in this special issue highlights the ability to incorporate fluid flow with endothelial cell-lined channels in a multicellular, extracellular matrix environment for dynamically probing molecular mechanisms of angiogenesis that are unmatched by other in vitro approaches. [1][2][3] The last article in this group further showcases the potential for coupling microfluidics with traction force microscopy to study mechanotransduction. 4 The next group of articles emphasizes the use of microfluidics for evaluating blood cell deformability and aggregation during network perfusion with a focus on gaining insights into the effects of sickle cell disease on altered red blood cell stiffness and function.…”
mentioning
confidence: 98%
“…While every model has its limitations and the debate over whether the added complexity afforded by microfluidic systems is sufficient to represent the in vivo scenario, the impact of microfluidics to angiogenesis and blood cell rheology research areas has been demonstrated (Figure ). The first group of articles in this special issue highlights the ability to incorporate fluid flow with endothelial cell‐lined channels in a multicellular, extracellular matrix environment for dynamically probing molecular mechanisms of angiogenesis that are unmatched by other in vitro approaches . The last article in this group further showcases the potential for coupling microfluidics with traction force microscopy to study mechanotransduction .…”
mentioning
confidence: 99%